Polycrystal Li2ZnTi3O8/C anode with lotus seedpod structure for high-performance lithium storage - Chen, Zhanjun; Wang, Tao; Liu, Meihuang; Duan, Panyu; Xiong, Feng; Zhou, Yang; Yan, Zhenyu; Yang, Wei; Chen, Han; Yang, Zhenyu; Li, Chao (Frontiers in Chemistry, 2023)
Lotus-seedpod structured Li2ZnTi3O8/C (P-LZTO) microspheres obtained by the molten salt method are reported for the first time. The received phase-pure Li2ZnTi3O8 nanoparticles are inserted into the carbon matrix homogeneously to form a Lotus-seedpod structure, as confirmed by the morphological and structural measurements. As the anode for lithium-ion batteries, the P-LZTO material demonstrates excellent electrochemical performance with a high rate capacity of 193.2 mAh g-1 at 5 A g-1 and long-term cyclic stability up to 300 cycles at 1 A g-1. After even 300 cyclings, the P-LZTO particles can maintain their morphological and structural integrity. The superior electrochemical performances have arisen from the unique structure where the polycrystalline structure is beneficial for shorting the lithium-ion diffusion path, while the well-encapsulated carbon matrix can not only enhance the electronic conductivity of the composite but also alleviate the stress anisotropy during lithiation/delithiation process, leading to well-preserved particles.